EFFECTS OF CLAY AND MOISTURE CONTENT ON SOIL-CORROSION DYNAMIC (Malaysian Journal of Civil Engineering, 2018)
Soil corrosion is a serious threat to the integrity of buried structures such as underground storage tanks, oil and gas transmission pipelines, and many other structures. This paper investigates the effects of soil engineering properties towards metal loss of buried X70 carbon steel coupons. The study focuses on soil engineering properties which are soil clay and moisture content. A number of 160 pieces of X70 carbon steel coupon were installed underground in five different locations in Peninsular Malaysia for 12 months period to study the influence of the above mentioned parameters towards metal loss caused by soil-corrosion. The samples were retrieved every 3 months to determine its weight loss and corrosion growth rate over time. The result shows that the rapid growth of corrosion is relatively correlated with the high moisture content of soil. Yet, corrosion initiated at a slow rate for clayey soil. Soil moisture content was found more influential towards corrosion dynamic as compared to clay content based on the qualitative evaluation.